De novo genes in Arachis hypogaea cv. Tifrunner: systematic identification, molecular evolution, and potential contributions to cultivated peanut. (4th July 2022) - Song, Hui; Guo, Zhonglong; Zhang, Xiaojun; Sui, Jiongming
SUMMARY: De novo genes are derived from non‐coding sequences, and they can play essential roles in organisms. Cultivated peanut ( Arachis hypogaea ) is a major oil and protein crop derived from a cross between Arachis duranensis and Arachis ipaensis . However, few de novo genes have been documented in Arachis . Here, we identified 381 de novo genes in A. hypogaea cv. Tifrunner based on comparison with five closely related Arachis species. There are distinct differences in gene expression patterns and gene structures between conserved and de novo genes. The identified de novo genes originated from ancestral sequence regions associated with metabolic and biosynthetic processes, and they were subsequently integrated into existing regulatory networks. De novo paralogs and homoeologs were identified in A. hypogaea cv. Tifrunner. De novo paralogs and homoeologs with conserved expression have mismatching cis ‐acting elements under normal growth conditions. De novo genes potentially have pluripotent functions in responses to biotic stresses as well as in growth and development based on quantitative trait locus data. This work provides a foundation for future research examining gene birth processes and gene function in Arachis and related taxa. Significance Statement: De novo genes were identified in Arachis hypogaea cv. Tifrunner. The present work provides key insights into the evolution and function of de novo genes in peanut.